Building Tolerance Attitudes Of PPKN Students Through Multicultural Education Courses - Jagad Aditya Dewantara; T Heru Nurgiansah (Universitas of Muhammadiyah Makassar, 2021)
Abstract. Lately ethnocentric attitudes or understand the area in the college environment are increasing. Discrimination against Sara is still occurring. If this is continued, it will further create division between the nation's children. This research aims to build tolerance among students to create unity and unity through the provision of Multicultural Education courses. This research uses qualitative methods with technical data collection through observation, interviews, documentation, and literacy studies. The results of this study show that multicultural education courses have managed to form a tolerance attitude among students of Pancasila Education and Citizenship of PGRI University Yogyakarta. Student tolerance is reflected in the implementation of lectures in the classroom, during the work of both individuals and groups, and during the implementation of the Final Semester Exam.Keywords: Tolerance; Student; Multicultural EducationAbstrak. Akhir-akhir ini sikap etnosentris atau faham kedaerahan di lingkungan perguruan tinggi semakin meningkat. Diskriminasi atas sara masih terjadi. Jika hal ini terus menerus dibiarkan akan semakin menimbulkan perpecahan antar anak bangsa. Penelitian ini bertujuan untuk membangun sikap toleransi dikalangan mahasiswa agar terciptanya persatuan dan kesatuan melalui pemberian mata kuliah Pendidikan Multikultural. Penelitian ini menggunakan metode kualitatif dengan tekniik pengumpulan data melalui observasi, wawancara, dokumentasi, dan studi literasi. Hasil penelitian ini menunjukan bahwa mata kuliah Pendidikan Multikultural telah berhasil membentuk sikap toleransi dikalangan mahasiswa Pendidikan Pancasila dan Kewarganegaraan Universitas PGRI Yogyakarta. Sikap toleransi mahasiswa tercermin saat pelaksanaan perkuliahan di kelas, saat pengerjaan tugas baik individu maupun kelompok, dan pada saat pelaksanaan Ujian Akhir Semester.Kata Kunci: Toleransi; Mahasiswa; Pendidikan Multikultural